2021
DOI: 10.1080/20008198.2021.1953788
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the frequency of intrusive memories after 24 hours using a visuospatial interference intervention: a follow-up and extension

Abstract: Background There is a need for effective, low-cost, readily available measures for reducing trauma symptoms so that people exposed to potentially traumatic events can receive help more quickly. A previous study reported that performing an intervention including a visuospatial task shortly after a reminder of a series of unpleasant film clips seen 24 hours earlier reduced the number of intrusive memories over the following week. Objective This study reports a follow-up a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Finally, findings of James et al (2015) have been independently replicated by Badawi et al (2020) who received training and feedback on the procedure from the authors of the original study. However, another study with several procedural variations and less training showed null effects (Brennen et al, 2021). This underscores the importance of establishing boundary conditions around an intrusion reduction effect, whether by examining variations in methods' details, or by examining individual differences that may impact the intervention engagement, as in the current study.…”
Section: Exposure To Analog Traumamentioning
confidence: 54%
“…Finally, findings of James et al (2015) have been independently replicated by Badawi et al (2020) who received training and feedback on the procedure from the authors of the original study. However, another study with several procedural variations and less training showed null effects (Brennen et al, 2021). This underscores the importance of establishing boundary conditions around an intrusion reduction effect, whether by examining variations in methods' details, or by examining individual differences that may impact the intervention engagement, as in the current study.…”
Section: Exposure To Analog Traumamentioning
confidence: 54%
“…As for visuospatial games, although it has been repeatedly reported that playing Tetris game can reduce the number of intrusions in experimental conditions ( 19 , 31 , 49 , 53 , 76 , 77 ), real-world traumas ( 20 , 21 , 75 , 78 ), and PTSD patients ( 22 ), and in either the consolidation (1920, 31, 73) or the reconsolidation time window ( 22 , 49 , 53 , 77 ), there were some studies finding null results with Tetris game ( 30 ) or visuospatial tasks either quite similar to ( 28 ) or different from ( 28 , 29 ) Tetris. One of the important reasons they attributed to for the null results was the possibility of less interesting and attention-grabbing of games, which is the basis of flow state.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis for the effectiveness of visuospatial tasks is that most intrusive memories are visual imageries ( 23 , 24 ), thus can be selectively disrupted by taxing working memory via competition for limited cognitive resources ( 25 27 ) when that memory is labile. However, this theory was challenged by some researches with negative results ( 28 , 29 ), and also the effects of Tetris game play could not be replicated by some researchers ( 30 , 31 ). These results indicate that there may be some boundary conditions that are subtle and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Data from 11 experiments (Badawi et al, 2020;Hagenaars et al, 2017;Holmes et al, 2010;James et al, 2015;H. Kessler et al, 2020;Lau-Zhu et al, 2019Page & Coxon, 2017) suggest playing Tetris effectively reduces intrusions (in a daily diary) whereas four do not (Asselbergs et al, 2018;Brennen et al, 2021;Brühl et al, 2019;Hemi et al, 2023). Thus, at first sight, most findings seem to corroborate the effectiveness of playing Tetris on the occurrence of intrusions.…”
Section: Introductionmentioning
confidence: 99%